How fast is protein hydrophobic collapse? - Sadqi, Mourad (National Academy of Sciences, 2003)
One of the most recurring questions in protein folding refers to the interplay between formation of secondary structure and hydrophobic collapse. In contrast with secondary structure, it is hard to isolate hydrophobic collapse from other folding events. We have directly measured the dynamics of protein hydrophobic collapse in the absence of competing processes. Collapse was triggered with laser-induced temperature jumps in the acid-denatured form of a simple protein and monitored by fluorescence resonance energy transfer between probes placed at the protein ends. The relaxation time for hydrophobic collapse is only ≈60 ns at 305 K, even faster than secondary structure formation. At higher temperatures, as the protein becomes increasingly compact by a stronger hydrophobic force, we observe a slowdown of the dynamics of collapse. This dynamic hydrophobic effect is a high-temperature analogue of the dynamic glass transition predicted by theory. Our results indicate that in physiological conditions many proteins will initiate folding by collapsing to an unstructured globule. Local motions will presumably drive the following search for native structure in the collapsed globule.